DNA damage and arterial hypertension. A systematic review and meta-analysis - Hazukova, Radka; Rezacova, Martina; Pleskot, Miloslav; Zadak, Zdenek; Cermakova, Eva; Taborsky, Milos (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2024)
Oxidative DNA damage markers (8OHdG, comet assay, gammaH2AX) are becoming widely used in clinical cardiology research. To conduct this review of DNA damage in relation to hypertension in humans, we used databases (e.g. PubMed, Web of Science) to search for English-language publications up to June 30, 2022 and the terms: DNA damage, comet assay, gammaH2AX, 8OHdG, strand breaks, and arterial hypertension. Exclusion criteria were: children, absence of relevant controls, extra-arterial hypertensive issues, animal, cell lines. From a total of 79526, 15 human studies were selected. A total of 902 hypertensive patients (pts): (comet: N=418 pts; 8OHdG: N=484 pts) and 587 controls (comet: N=203; 8OHdG: N=384) were included. DNA damage was significantly higher in hypertensive pts than healthy controls (comet 26.6±11.0 vs 11.7±4.07 arbitrary units /A.U./; P<0.05 and="" 8ohdg="" 13="" 1="" 4="" 12="" vs="" 6="" 97="" 2="" 67="" ng="" mg="" creatinine="" i=""> P<0.05) confirmed with meta-analysis for both. Greater DNA damage was observed in more adverse cases (concentric cardiac hypertrophy 43.4±15.4 vs 15.6±5.5; sustained/untreated hypertension 31.4±12.1 vs 14.2±5/35.0±5.0 vs 25.0 ±5.0; non-dippers 39.2±15.5 vs 29.4±11.1 A.U.; elderly 14.9±4.5 vs 9.3±4.1 ng/mg creatinine; without carvedilol 9.1±4.2 vs 5.7±3.9; with coronary heart disease 0.5±0.1 vs 0.2±0.1 ng/mL) (P<0.05) confirmed with meta-analysis. DNA damage correlated strongly positively with serum glycosylated haemoglobin (r=0.670; P<0.05) and negatively with total antioxidant status (r=-0.670 to -0.933; P<0.05). This is the first systematic review with meta-analysis showing that oxidative DNA damage was increased in humans with arterial hypertension compared to controls.
Keywords: DNA Damage; hypertenze; Female; oxidační stres; biologické markery; Biomarkers; cardiovascular disease; 8-hydroxy-2'-deoxyguanosin; ženské pohlaví; Oxidative Stress; lidé; 8-Hydroxy-2'-Deoxyguanosine; 8OHdG; gammaH2AX; DNA strand break damage; poškození DNA; Hypertension; Male; Comet Assay; comet assay; arterial hypertension; kometový test; mužské pohlaví; Humans